Einen neuen Staat bauen. Die Entwicklung des polnischen Schienennetzes in der Zwischenkriegszeit - Elias Oppenrieder (Zeitschrift für Ostmitteleuropa-Forschung, 2024)
This article deals with the development of the Polish railway network in the interwar period. The then Polish state, the Second Polish Republic, had to face two challenges in particular: Firstly, the railway network, built before World War I, had been constructed by the partitioning powers Russia, Prussia, and Austria-Hungary according to their own needs. Secondly, the network had sustained extensive damage as a result of combat actions during the war. Accordingly, the paper analyzes, on the one hand, how the decisive actors of the Second Polish Republic attempted to repair this damage to the railway network. On the other hand, their endeavors to adapt the railway network to the infrastructural demands of the new state are explored, with a focus on the construction of new railway lines. Starting with an overview of the development of the Polish railway network in the interwar period in both temporal and spatial regard, the paper proceeds with an in-depth analysis of selected case studies. To sum up, the study shows that while many new railway lines were built in the interwar period, an adaption of the railway network to the needs of the new state was achieved merely in part.